Post-interactive communication A study to build a model for the flow of communication in social networking sites - Harmaz, Marlen Auwash (ALBAHITH ALALAMI, 2022)
The issue of the research lies in the non-representation of the models developed for the communication process in the interaction and networking processes through social media, as the research sought to build a network model of communication according to the specific data and features of social media platforms in order to reach a special generalization to understand how the process of networking operates in cyberspace. The researcher followed the analytical survey approach as she described the communication models outwardly in order to be able to build a networked communication model that represents the flow of post-reactive communication. Therefore, it has been named "Nebula - Sadeem" after the concept of post-space and cosmic galaxies in which is similar in meaning to the post-networked interaction that occurs in cyberspace. The research concluded to form a communication model of the intermediate level, and it is classified within circular models with infinite spiral shape, which is represented by the verification of the hypothesis, which states that communication via social networking combines the linear and interactive models, considering the sender’s access to the network and contact with another person The communication is linear and when the interaction occurs with its publications, the communication becomes circular (interactive). As well as representing the process of symbolizing the meanings in a message that is being interacted with by individuals from different affiliations but share similar interests about the content provided at the original sending point. This interaction will lead to widening the connection in an infinite spiral circularly manner. The interaction of the users with the publication will move it from its original point to another point in the cyberspace. Subsequently, there will be a new process of interaction represented by a new spiral communication circuit that may be larger or smaller than the original circuit.